Repurposing of the Antiepileptic Drug Levetiracetam to Restrain Neuroendocrine Prostate Cancer and Inhibit Mast Cell Support to Adenocarcinoma - Sulsenti, Roberta; Frossi, Barbara; Bongiovanni, Lucia; Cancila, Valeria; Ostano, Paola; Fischetti, Irene; Enriquez, Claudia; Guana, Francesca; Chiorino, Giovanna; Tripodo, Claudio; Pucillo, Carlo E.; Colombo, Mario P.; et al. (Frontiers in Immunology, 2021)
A relevant fraction of castration-resistant prostate cancers (CRPC) evolve into fatal neuroendocrine (NEPC) tumors in resistance to androgen deprivation and/or inhibitors of androgen receptor pathway. Therefore, effective drugs against both CRPC and NEPC are needed. We have previously described a dual role of mast cells (MCs) in prostate cancer, being capable to promote adenocarcinoma but also to restrain NEPC. This finding suggests that a molecule targeting both MCs and NEPC cells could be effective against prostate cancer. Using an in silico drug repurposing approach, here we identify the antiepileptic drug levetiracetam as a potential candidate for this purpose. We found that the protein target of levetiracetam, SV2A, is highly expressed by both NEPC cells and MCs infiltrating prostate adenocarcinoma, while it is low or negligible in adenocarcinoma cells. In vitro, levetiracetam inhibited the proliferation of NEPC cells and the degranulation of MCs. In mice bearing subcutaneous tumors levetiracetam was partially active on both NEPC and adenocarcinoma, the latter effect due to the inhibition of MMP9 release by MCs. Notably, in TRansgenic Adenocarcinoma of the Mouse Prostate (TRAMP) mice subjected to surgical castration to mimic androgen deprivation therapy, levetiracetam reduced onset and frequency of both high grade prostatic intraepithelial neoplasia, adenocarcinoma and NEPC, thus increasing the number of cured mice showing only signs of tumor regression. Our results demonstrate that levetiracetam can directly restrain NEPC development after androgen deprivation, and that it can also block adenocarcinoma progression through the inhibition of some MCs functions. These findings open the possibility of further testing levetiracetam for the therapy of prostate cancer or of MC-mediated diseases.